360-degree video in education: an overview of the literature - Bruni , Isabella; Ranieri , Maria; Luzzi , Damiana (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2021)
For years now, the need for renewal of higher education has been discussed at a national and international level, with a focus on both new teaching methods and technological innovations. The integration and use of ICTs can, in fact, represent a catalyst for wider processes of improvement of the teaching-learning process, with implications not only at organizational and communication level, but also in terms of increasing students’ protagonism and collaboration. Among the latest generation of tech-nologies, a particularly interesting area is that of immersive environments, ranging from augmented to virtual reality. According to recent literature, they may have a positive impact both in terms of involvement and transfer of knowledge into real contexts. In this article, the focus is on 360-degree video technology: through the systematic analysis of the literature here presented, their educational uses will be highlighted, especially with respect to the university.